Transcranial low-intensity ultrasound stimulation for treating central nervous system disorders: A promising therapeutic application - Hu, Yun-Yun; Yang, Gang; Liang, Xue-Song; Ding, Xuan-Si; Xu, De-En; Li, Zhe; Ma, Quan-Hong; Chen, Rui; Sun, Yan-Yun (Frontiers in Neurology, 2023)
Transcranial ultrasound stimulation is a neurostimulation technique that has gradually attracted the attention of researchers, especially as a potential therapy for neurological disorders, because of its high spatial resolution, good penetration depth, and noninvasiveness. Ultrasound is divided into high-intensity and low-intensity ultrasound according to the intensity of its acoustic wave. High-intensity ultrasound can be used for thermal ablation by taking advantage of its high-energy characteristics. Low-intensity ultrasound, which produces low energy, can be used as a means to regulate the nervous system. The present review describes the current status of research on low-intensity transcranial ultrasound stimulation (LITUS) in the treatment of neurological disorders such as epilepsy, essential tremor, depression, Parkinson's disease (PD) and Alzheimer's disease (AD). This review summarizes the preclinical and clinical studies using LITUS in the treatment of the above mentioned neurological disorders and discusses the underlying mechanisms.